The Use of Social Media as a Provocation Tool: A Case Analysis of Pope Francis' Visit to Indonesia - Evelin, Vanesca; Aristoteles; Yurika F. Dewi (Dinasti Research, 2025)
This study discusses the use of social media as a provocation tool in the context of Pope Francis' visit to Indonesia. The background of this research stems from the increasing potential of social media in spreading provocative information that can trigger social tensions, especially during sensitive moments such as the visit of a religious leader. The aim of this research is to identify the forms of provocation that emerge on social media and evaluate the effectiveness of criminal law, particularly the Information and Electronic Transactions Law (ITE Law) and the Criminal Code (KUHP), in addressing the spread of such provocative content. The research method used is qualitative with a juridical-normative approach, where data is collected through literature studies and content analysis of related social media. The findings indicate that social media is utilized by various groups to spread provocative narratives that can lead to social conflict. Furthermore, the enforcement of the ITE Law and KUHP in addressing criminal acts of spreading provocative content still faces challenges, particularly in law enforcement and public awareness. This study suggests the need for stronger legal regulations and education for social media users to reduce the negative impact of provocative content.